TRIPHENYL PHOSPHITE: A CANDIDATE FOR LIQUID POLYAMORPHISM - Senker J.; Rössler E. (My University, 2001)
We start giving a brief review on the current discussion of polyamorphism. In particular, the problems of experimentally identifying amorphous–amorphous or liquid–liquid transitions are considered, which are often related to the difficulty of proving the purely amorphous character of a modification. Usually methods probing the structure are used which inherently include the problem of length scales. The leading idea of the work presented here is to show that this problem may be overcome by, additionally, characterising the dynamical properties of a phase. As an example for our strategy, we chose triphenyl phosphite (TPP), which is a candidate for a liquid–liquid transition. This well-known organic glass former exhibits a first-order phase transition from the supercooled liquid to a second apparently amorphous phase. Results obtained from a variety of different techniques such as NMR, dielectric and Brillouin spectroscopy are presented. Although the reorientational dynamics present in the second amorphous phase is characterised by an unusual broad distribution of correlation times, the data compiled are compatible with the existence of two liquid phases.